2002
DOI: 10.1177/0360491802238705
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Presidents Fail?

Abstract: As part of the future research agenda for presidency scholars, this article deals with two distinct but related issues: the first involves failed presidential decision making, particularly in the employment of prerogative power; the second involves the failure of interbranch collaborative decision making. Such study of failed presidential decision making is a topic of inquiry related to, but somewhat distinct from, the question of the "failed presidency" that has already engaged some presidency scholars. In so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…One variant of this phenomenon can be found in the apparent paradox of the modern presidency: even as the president has amassed greater institutional resources than his nineteenth century forerunners, the modern president also appears more constrained than his predecessors in the face of other institutional actors confident in their constitutional roles and more vigilant in their efforts to defend them. 134 In addressing this question, future research might examine how changes in the structure of political competition, such as the role of political parties as mediating institutions, impact political barriers to entry in the United States. In congressional politics for example, scholars have shown that ballot access rules such as filing fees and petitions do erect political entry barriers and discourage competition.…”
Section: Political Entrepreneurship Institutional Change and Americmentioning
confidence: 99%
“…One variant of this phenomenon can be found in the apparent paradox of the modern presidency: even as the president has amassed greater institutional resources than his nineteenth century forerunners, the modern president also appears more constrained than his predecessors in the face of other institutional actors confident in their constitutional roles and more vigilant in their efforts to defend them. 134 In addressing this question, future research might examine how changes in the structure of political competition, such as the role of political parties as mediating institutions, impact political barriers to entry in the United States. In congressional politics for example, scholars have shown that ballot access rules such as filing fees and petitions do erect political entry barriers and discourage competition.…”
Section: Political Entrepreneurship Institutional Change and Americmentioning
confidence: 99%
“…Richard Pious in a 2002 article called “Why Do Presidents Fail?”—later expanded to a book in 2008—said it was time to revisit many of Neustadt's formulations, such as his distinction between the “amateur” president (Eisenhower) who first thinks of the public interest and his political stakes, and the “professional” (FDR) who defines the public interest in terms of his political advantage (Pious 2002; Pious 2008). In his book version, Pious says that Neustadt engaged in a “sleight of hand” by arguing that the president should define public policy “in terms of his own power stakes, because that is the professional way to develop the most viable public policy.” But why, Pious asked, would those he is attempting to persuade want to comply with a policy simply because it is in the president's personal interest?…”
Section: Presidential Studies After September 11mentioning
confidence: 99%
“…In his book version, Pious says that Neustadt engaged in a “sleight of hand” by arguing that the president should define public policy “in terms of his own power stakes, because that is the professional way to develop the most viable public policy.” But why, Pious asked, would those he is attempting to persuade want to comply with a policy simply because it is in the president's personal interest? (Pious 2008, 262). Earlier, in 1984, Pious joined with Christopher Pyle to write an excellent study, The President, Congress, and the Constitution (Pyle and Pious 1984).…”
Section: Presidential Studies After September 11mentioning
confidence: 99%
“…They are crisis managers, not policy planners, and often find it necessary to devote more time to petty urgencies than to important matters, like restoring the rule of law. As crisis managers, presidents have little choice but to entrust enormous powers to people they hardly know, who will, in time, find it expedient to accept most of their agency's goals and confine reformist urges to a few select issues (Pious ).…”
Section: Continued Secrecymentioning
confidence: 99%